The Changing Contours of Maritime Security in The South China Sea - Mr. Muhammad Waqar Anwar (CISS Insight Journal, 2017)
The South China Sea (SCS) is one of the most significant regions of the world. As the main passageway between the Indian and Pacific Oceans, the Sea carries one-third of global maritime trade1. Therefore, many countries, and particularly the countries that have a stake in maritime commerce are concerned about the safety and security of the transit of goods. The change in US approach in 2010 which is known as the ’Asia Pivot’ or rebalancing strategy has prompted a renewed focus on the SCS, as the rebalancing arrangement incorporated a military segment also. The US declared the moving of 60 percent of its maritime capability to the Asia Pacific. This aspect has considerably added to the strategic significance of the SCS. The SCS is a partially enclosed sea formed by seven littoral states: China, Taiwan, Vietnam, Malaysia, Brunei, Indonesia and the Philippines. The SCS extends from Taiwan in the north to the waters contiguous to Indonesia and the Straits of Malacca and Singapore in the south. The SCS has 200 small islets, rocks, and reefs spread over 1,700 miles. After Chinese occupation of the Spratly Islands in 1974, a Chinese journal highlighted the importance of the SCS ‘as lying between the Indian Ocean and the Pacific, and performing the function of a doorway to the outside world for the landmass and the littoral islands of China’.2 Moreover, the recent tensions in the SCS with the naval presence of China and the US and other developments have further increased the geostrategic importance by a great degree.